Rail and Subway Concessions in Rio de Janeiro - Rebelo, Jorge M. (World Bank, Washington, DC, 2012)
To help address a budgetary crisis in early 1995, the Rio de Janeiro state government began reforms aimed at selling or concessioning to the private sector loss-making state-owned enterprises. In the transport sector this meant selling or concessioning subway, commuterrail, bus, and ferry services, at the time requiring subsidies of US $363 million annually. This note describes the concessioning of Rio's subway, the Metro, in December 1997 and its commuter rail service, Flumitrens, in July 1998. Together they accounted for 80 percent of the subsidies. The reform was expected to eliminate subsidies for the Metro and reduce them by two-thirds for Flumitrens, to improve service, and to clear the backlog of maintenance and investment.